2015
DOI: 10.5603/fhc.a2018.0003
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical mapping of neurotensin in the alpaca diencephalon

Abstract: In comparison with other mammals, the thalamus of the alpaca showed the most widespread distribution of neurotensin-immunoreactive fibers. The widespread distribution of neurotensin through the alpaca diencephalon suggests that the peptide can be involved in many physiological actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Using a freezing microtome, 40-45 µm-thick brain coronal sections were obtained and processed for immunocytochemistry. [8][9][10] As previously described [8][9][10]30,31 and in order to inactivate the endogenous peroxidases, sections were pre-incubated in a mixture solution of methanol/H 2 O 2 (2v/1v) for 30 min. Then, sections were washed three times with PBS for 30 min and pre-incubated in a PBS solution containing 0.3% Triton X-100 and supplemented with 1% of normal horse serum (mixture solution) for 30 min.…”
Section: Immunocytochemical Studymentioning
confidence: 99%
“…Using a freezing microtome, 40-45 µm-thick brain coronal sections were obtained and processed for immunocytochemistry. [8][9][10] As previously described [8][9][10]30,31 and in order to inactivate the endogenous peroxidases, sections were pre-incubated in a mixture solution of methanol/H 2 O 2 (2v/1v) for 30 min. Then, sections were washed three times with PBS for 30 min and pre-incubated in a PBS solution containing 0.3% Triton X-100 and supplemented with 1% of normal horse serum (mixture solution) for 30 min.…”
Section: Immunocytochemical Studymentioning
confidence: 99%
“…In addition to those works focused on the alpaca reproductive mechanisms, several studies have been previously performed on the neuroanatomical location of neuropeptides (calcitonin gene-related peptide, somatostatin-28 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), neurotensin, leucine-enkephalin, alphaneo-endorphin, adrenocorticotropic hormone (18-39), beta-endorphin ) in the alpaca brainstem [17][18][19][20][21][22]. In addition, a recent study has shown a close neuroanatomical relationship between the enkephalinergic (methionine-enkephalin) and tachykininergic (substance P) systems in the alpaca diencephalon and the presence of some neuropeptides (e.g., neurotensin) has also been reported in this region of the alpaca CNS [5,23]. To our best knowledge no immunohistochemical study on the distribution of SP and MET has been carried out in the alpaca brainstem.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2007, the immunohistochemical mapping of several neuropeptides has been performed in the alpaca ( Lama pacos ) brainstem and diencephalon (Coveñas et al., , ; Manso et al., ; Marcos, Arroyo‐Jiménez, Lozano, Aguilar, & Coveñas, ; Marcos et al., ; Sánchez et al., ; de Souza, Sánchez, Aguilar, Díaz‐Cabiale, & Narváez, ; de Souza et al., , , ). In the brainstem of this species, the distribution of fibres/cell bodies containing leucine‐enkephalin, calcitonin gene‐related peptide, neurotensin or somatostatin 28 (1–12) is currently known (Marcos et al., ; de Souza et al., , , , ).…”
Section: Introductionmentioning
confidence: 99%